Irritation Test using the HET-CAM Method on A Sunscreen Formulation Containing A Combination of Tea Tree Oil and Raspberry Oil - Nadia Miftahul Jannah; Septia Faranggi (Journal of Food and Pharmaceutical Sciences, 2026)
Exposure to ultraviolet (UV) radiation and the risk of skin irritation are major challenges in the development of modern skincare products. Sunscreens not only serve to protect the skin from UV radiation but must also meet safety requirements and be non-irritating. Tea tree oil (Melaleuca alternifolia) possesses anti-inflammatory, antimicrobial, and wound-healing properties, while raspberry oil (Rubus idaeus) is rich in antioxidants, vitamin E, and essential fatty acids beneficial for skin health. The combination of these two oils has the potential to enhance sunscreen effectiveness while providing additional natural anti-inflammatory benefits. This study aims to evaluate the irritation effect of a sunscreen cream formulation containing a combination of tea tree oil and raspberry oil using the HET-CAM (Hen’s Egg Test–Chorioallantoic Membrane) method. This method was chosen because it can mimic vascular responses similar to human skin, where parameters such as hemorrhage, coagulation, and membrane damage serve as indicators of irritation levels. The results of this study are expected to provide scientific information regarding the safety of the combined essential oils and support the development of safe, effective, and natural cosmetic products with anti-inflammatory sunscreen potential.